Examining Disparities in Case Dispositions and Sentencing Outcomes for Domestic Violent Extremists in the United States - Gruenewald, Jeff (Crime & delinquency, 2024)
This study examines how strength of ideology, victim status, and other factors shape prosecutorial and sentencing decisions in cases of far-right extremist homicide. We draw from multiple conceptual frameworks to understand how assessments of defendants? blameworthiness, crime seriousness, and other practical constraints influence the severity of legal outcomes. Our analysis of data from the United States Extremist Crime Database finds that while demographic attributes of homicide participants have little influence on legal outcomes, strong affiliations to domestic extremism and indicators of crime seriousness and risk significantly predict harsher treatment of defendants. We contextualize our findings within the broader criminological sentencing literature and discuss their implications for understanding how the American criminal justice system responds to domestic violent extremism.